Prospects on searches for baryonic Dark Matter produced in b-hadron decays at LHCb - Brea Rodríguez, Alexandre; Chobanova, Veronika; Cid Vidal, Xabier; López Soliño, Saúl; Martínez Santos, Diego; Mombächer, Titus; Prouvé, Claire; Rodríguez Fernández, Emilio Xosé; Vázquez Sierra, Carlos (The European physical journal. C, Particles and fields, 2021)
A model that can simultaneously explain Dark Matter relic density and the apparent matter anti-matter imbalance of the universe has been recently proposed. The model requires b -hadron branching fractions to Dark Matter at the per mille level. The b -hadrons decay to a dark sector baryon, ψ DS , which has a mass in the region 940 MeV / c 2 ≤ m ψ DS ≤ 4430 MeV / c 2 . In this paper, we discuss the sensitivity of the LHCb experiment to search for this dark baryon, covering different types of topology and giving prospects for Runs 3 and 4 of the LHC, as well as for the proposed Upgrade II. We show that the LHCb experiment can cover the entire mass range of the hypothetical dark baryon.